Anti-Tax Avoidance Rules and Tax Complexity - Schanz, Deborah; Siegel, Felix; Sureth-Sloane, Caren (World Tax Journal)

Liquiditätseffekte einer Vermögensteuer bei Mietwohnimmobilien - Maiterth, Ralf; Piper, Yuri; Sureth-Sloane, Caren (Steuer und Wirtschaft)
Dieser Beitrag untersucht Liquiditätseffekte einer Vermögensteuer bei Mietwohnimmobilien. Mithilfe von Daten einer Immobilien-Kapitalgesellschaft werden die Wirkungen einer Vermögensteuer auf die Cashflows aus der Vermietung von Wohnimmobilien simuliert. Der Detailgrad der Daten ermöglicht dabei Analysen auf Jahres-, Regional- und Baujahresebene. Ein Abgleich mit weiteren Immobiliendaten untermauert die Vergleichbarkeit und Aussagekraft der Analysen. Die Ergebnisse der Simulation zeigen, dass die Einführung einer Vermögensteuer den Cashflow aus dem Mietgeschäft erheblich reduzieren und zu Liquiditätsproblemen führen kann. Im Durchschnitt über alle Beobachtungen ergibt sich bei einem Vermögensteuersatz i.H.v. 2 % ein negativer Cashflow nach Berücksichtigung aller Kosten. Generell bedeutet dies, dass wachstumsorientierte Immobilien durch eine Vermögensteuer liquiditätsmäßig stärker belastet werden als mietrenditeorientierte Immobilien. Insbesondere in Großstädten mit hohen Immobilienwerten, aber verhältnismäßig geringen Mieten, können die Liquiditätseffekte mehr als dreimal so hoch ausfallen wie in ländlichen bzw. industriell-geprägten Regionen, was zu einem relativen Attraktivitätsverlust führen kann. Durch die Entkopplung der Vermögensteuer von den Mieterträgen zeichnet sich eine starke Abhängigkeit der Steuerlast von aktuellen Marktentwicklungen und dem Zinsumfeld ab, was eine zusätzliche Unsicherheit für Investoren darstellt. Diese steuerliche Unsicherheit könnte sich potentiell auf die Investitionsbereitschaft auswirken und sollte daher in politischen Diskussionen über die Wiedereinführung einer Vermögensteuer berücksichtigt werden.

Steuern und Steuergerechtigkeit – Ein Gespräch - Schönhärl, Korinna; Sureth-Sloane, Caren (Ethik und Gesellschaft)

Beer, Cars & Fundamentals: Predicting German M& A activity - Sievers, Sönke; Li, Reeyarn; Degen, Dominik; Kengelbach, Jens; Pietrogrande, Francesca
This paper introduces a predictive model for German mergers and acquisitions (M& A) activity leveraging deep feedforward neural networks (DFNN) incorporating well-established traditional variables (also known as features), along with a ChatGPT-based M& A sentiment score (MASS) and unconventional predictors such as beer sales and weather data. We demonstrate that the inclusion of sentiment and non-traditional variables enhances predictive performance. Our findings provide an important empirical foundation for understanding near-term fluctuations in German M& A activity and offer a forecasting tool relevant to both practitioners and researchers.

Trinity and Empathy. The modern renewal of Trinitarian ontology and the experience of empathy in the phenomenology of Edith Stein - König, Katrin (Engaging nicene trinitarianism : historical analysis, theological exploration, and contemporary relevance)

Rezension zu Dominik Balg: Wissen, was gut ist. Moralische Bildung im Spannungsfeld zwischen Manipulation und Beliebigkeit - Kaup, Michael (Zeitschrift für Didaktik der Philosophie und Ethik (ZDPE))

The Co-CALIBRATE Framework: An Evidence-Based Framework for the Cultural Adaptation of Brain Injury Intervention Tools with Stakeholder Engagement. - Quinting, J.; Avramovic, P.; Brassel, S.; Brunner, B.; Jonas, Kristina; Rietdijk, R.; Rubi-Fessen, I.; Stenneken, P.; Togher, L.

Das Co-CALIBRATE Framework: Ein international konsentiertes, evidenzbasiertes Framework für kultur-sensitive Adaptationen von Therapie-Ressourcen im Bereich Sprach- und Kommunikationsstörungen nach Hirnschädigungen - Quinting, J.; Avramovic, P.; Brassel, S.; Brunner, M.; Jonas, Kristina; Rietdijk, R.; Rubi-Fessen, I.; Stenneken, P.; Togher, L. (Jahrestagung der Gesellschaft für Aphasieforschung und -behandlung (GAB) e.V., Aachen.)

Solving Polynomial Equations Over Finite Fields - Dell, Holger; Haak, Anselm; Kallmayer, Melvin; Wennmann, Leo (Proceedings of the 2025 Annual ACM-SIAM Symposium on Discrete Algorithms (SODA))

Education as negotiation? Lessons to be learned from the social side(s) of sustainable renewable energy development in East Africa - Asiimwe, Henry; Freitag, Christine; Mangeni, Teddy (Bildung für nachhaltige Entwicklung: Kontroversen und Debatten)

Rezension zu: Bräuer, Benjamin: Historische Orientierungsgelegenheiten. Wie Irritationen historisches Denken anregen. Stuttgart 2024 - Pilz, Franziska

Co-CALIBRATE: An Evidence-Based Framework For The Cultural Adaptation of Brain Injury Intervention Tools With Stakeholder Engagement - Quinting, J.; Avramovic, P.; Brassel, S.; Brunner, M.; Jonas, Kristina; Rietdijk, R.; Rubi-Fessen, I.; Stenneken, P.; Togher, L. (15. World Congress on Brain Injury, Montreal, Canada)

Der Weg als Ziel: Die Gestaltung von Transferprozessen in Innovationsprogrammen am Beispiel InnoVET - Daniel-Söltenfuß, Desiree (BWP@: Berufs- und Wirtschaftspädagogik - online)

Intrinsic lubrication: A new approach in the context of the deep drawing process - Cakici, Ermir; Homberg, Werner (Materials Research Proceedings)
Abstract. This study presents intrinsic lubrication as a novel approach to deep drawing processes, using additively manufactured, lubricant-permeable tools to minimize lubricant consumption and improve efficiency. Two systems were evaluated: a passive system based on capillary action and gravity, and an active system using pumped delivery for precise, on-demand application. Experimental tests were conducted on micro-bores (0.2-0.5 mm) to demonstrate their suitability for lubricant transport. Smaller bores have excellent capillary action but are prone to clogging, while larger bores offer higher permeability. The passive system is resource-efficient but requires adjustments to counteract gravitational asymmetry. The active system provides consistent lubricant distribution but is more complex. These findings provide a basis for optimizing intrinsic lubrication systems.

Islamic Principles of Tolerance and Its Relevance for an Islamic Religious Pedagogy -Teaching ›Tolerance‹ in a Contemporary Islamic Education Context: Observations on Semantical Differentiations of Terms and Meanings - Kokew, Stephan Matthias (Islamic Theological and Pedagogical Approaches to Religious Education. Interdisciplinary Perspectives on Contemporary Challenges)
Keywords: Tolerance; Islamic Tradition

Introduction - Freitag, Christine; Temmen, Katrin (Sustainable Energy Development in East Africa: Interdisciplinary Approaches)

Sustainable Energy Development in East Africa: Interdisciplinary Approaches

Boyken, Thomas/Anna Stemmann (Hgg.): Vom Mund- und Handwerk. Mündliches und schriftliches Erzählen in kinder- und jugendliterarischen Texten. Stuttgart: Metzler 2022 (Studien zu Kinder- und Jugendliteratur und -medien - Kanning, Julian (kjl&m)

Zwischen Ablehnung und Befürwortung . Professionelle Beliefs zu Holocaust-Bilderbüchern im Unterricht von Klasse 4 - Iris, Kruse; Kanning, Julian (Praktiken der Erinnerung)

INNOVADE Press Release: INNOVADE publishes an Interdisciplinary Knowledge Base on Digital Democracy - Fuchs, Christian